Recommended diagnosis and management of insomnia. Issue 1 (January 2014) - Wilson, Sue; Nutt, David
Abstract: Insomnia can cause impaired daytime functioning and reduced quality of life. In our Drug review the authors discuss its diagnosis and the available treatment options, followed by an analysis of the prescription data and sources of further information.